The Effect of Work Environment, Work-Life Balance, and Employee Engagement on Employee Loyalty - Kurniawati, Ayu Febrina; Nuvriasari, Audita (LifeSciFi, 2025)
This study aims to analyze the influence of the work environment, work-life balance, and employee engagement on employee loyalty. The study uses a quantitative approach with IBM SPSS Statistics 29 for validity and reliability tests. It was conducted at PT. Kebun Teh Region W, with a population of 214 employees. The research sample consisted of 59 employees, selected using the purposive sampling method. The results of the study indicate that the work environment has a positive and significant effect on employee loyalty. This suggests that a conducive and supportive work environment can foster employee commitment. Similarly, work-life balance has a positive and significant effect on employee loyalty, meaning that employees who can balance their professional and personal responsibilities tend to be more loyal to the company. Furthermore, employee engagement also has a positive and significant effect on employee loyalty, indicating that employees who are involved and feel appreciated and connected to their work are more likely to be committed to the organization. The study highlights the importance of a positive work environment, balanced work-life integration, and strong employee engagement in increasing employee loyalty, which is crucial for the success of an organization.